Orthodoxy and the myriad of challenges posed in the socio-economic sphere of Africa - His Grace Athanasios Akunda (RIP) (†) (Africajournals, 2021)
The above title does not only pause a challenge to us but also displays before us the celebration of our achievements in Africa which are worthy of celebration. In this paper therefore I will address the problems of Africa on social and economic ground in relation to culture. I addressed this issue before and have discussed it at length with my brother-in-Christ father Evangelos who is an ethicist. The social and economic problems are not entities in themselves but they each have a root cause and unless we address the roots we may not find any positive or lasting solutions. The root problem faced by many is a sense of cultural erosion which has led to lack of self-identity and thus resulted in many of the visible problems we are experiencing and we are desperately trying to find solutions to them. This problem may be self-inflicted as some of us may think but it is largely blamed on Religious missions in Africa from the past centuries to now, and also on the colonial powers who imposed themselves on Africa. The positive and negative effects of the two have left a great impact on an African way of thinking and acting. We have become aliens in our own African land, whether we are Black, Arab, White or Indian or whatever race of African. As each day dawns we are faced with the consequences of the past mistakes and even in trying to find solutions we repeat the same mistakes on an ongoing basis. I will discuss my reflection on several of these bases; 1) dialogue with African culture a) identity crisis, b) Cultural erosion c) Cultural disintegration d) family unit and social unit break ups and confusion, e.) Generation gap f.) Economic gap g.) Religious bias and mission misrepresentation h) indigenous languages, species i) Colonial Stigma j) Economic imbalance and trade unfairness.